Bancor Comes of Age: A Case for an Indian Bitcoin Reserve. (March 2022) - Komath, Ashwath
John Maynard Keynes proposed the concept of 'Bancor' in 1940 as a supranational currency that would serve as the international reserve currency. The concept did not take off at the time, despite the underlying need to liberate the international system from the hegemonic tendencies of a national currency serving as a global medium of exchange. The emergence of Bitcoin makes it possible to revive the idea of a de-nationalised global medium of exchange. This article examines the feasibility of such an idea by examining a viable state policy for adoption and use in the international realm.